Analysis of the Implementation of Full Day Calistung in Improving Ability (Reading, Writing, and Arithmetic) in Grade 1 Children at SDIT An-Nahl, Guguak District - Putri Natasya; Yane Trisnawati; Nabila Febrianti; Syaiful Marwan (Jurnal Masyarakat Religius dan Berwawasan, 2023)
The article writer uses a type of participatory action research method. This is because the PAR method is an action considered as "systematic and oriented towards data analysis whose answers require the collection and analysis of data and the generation of interpretations directly tested in the field of action involving action researchers and members of society or organizations who seek to improve their situation. This dedication The participatory action research method was chosen because in this service it is an activity carried out to see the educational process carried out in the community in the form of actions to improve their situation as in the field it was found that there were several children who were still unable to read, write and count. This service was carried out by providing learning assistance to children who are in elementary school at SDIT An-Nahl, especially lower class children, namely class I. The form of activity is learning to read, write and count (mathematics). namely class I where the number of children participating is around 20 children.